Implementasi Metode Sorogan dalam Meningkatkan Kemampuan Baca Al-Qur’an: Studi di MTs Takhasus Qur’an Alfalahiyah Lampung Timur - Kholifatul Muthoharoh; Nurul Aisyah; Ehwanudin Ehwanudin (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This study aims to determine the process of applying the sorogan method in improving ability to read of holy Koran at MTs Takhasus Qur’an Batanghari Lampung Timur. This study is a qualitative research and using case study aprroach. This study aims to make a description, picture or painting systematically, accurately and factually about implementation learning of holy koran using the sorogan method. Research subjects were principals, qur’anic teachers, and students. Data collection techniques in this study were observation, interviews, and documentation. Data analysis used source, technique and time triangulation. The results of this research are implementation of this method is quite effective to improving students' ability to read of holy Koran. However, a number of obstacles were found in the learning process, such as a lack of time for students who needed special attention, a shortage of teacher human resources, and the need for patience and perseverance.